1990
DOI: 10.1105/tpc.2.9.905
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Restoration Is Associated with Loss of a Portion of the Mitochondrial Genome in Cytoplasmic Male-Sterile Common Bean.

Abstract: Restoration of pollen fertility to cytoplasmic male-sterile common bean by nuclear gene Fr is accompanied by mitochondrial (mt) DNA rearrangements within restored plants. These rearrangements are also observed upon spontaneous cytoplasmic reversion to fertility. An mtDNA fragment of at least 25 kilobases was lost from the genome upon restoration or reversion. This fragment contained DNA segments that were not repeated elsewhere in the genome and, therefore, were not detected within the genome upon fertility re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…It has been documented that tissue culture may induce structural mutations of mitochondrial genes in plants (Sadoch et al 2000). The presence of the restorer gene (Fr) results in the permanent deletion of the mitochondrial CMS-inducing sequence (pvs) in common bean (Mackenzie and Chase 1990).…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that tissue culture may induce structural mutations of mitochondrial genes in plants (Sadoch et al 2000). The presence of the restorer gene (Fr) results in the permanent deletion of the mitochondrial CMS-inducing sequence (pvs) in common bean (Mackenzie and Chase 1990).…”
Section: Discussionmentioning
confidence: 99%
“…However, the stoichiometry can be changed by a phenomenon called substoichiometric shifting. Although substoichiometric shifting has been triggered by tissue culture (Kanazawa et al 1994), it has been more extensively studied in common beans where it is caused by nuclear factors such as the Fr locus (Mackenzie and Chase 1990;Janska et al 1998;Abdelnoor et al 2003). Recently, nuclear loci such as Msh1 (Abdelnoor et al 2006), RecA (Shedge et al 2007) and OSB1 (Zaegel et al 2006) were reported to suppress mtDNA recombination and maintain specific stoichiometry of sublimons.…”
Section: Introductionmentioning
confidence: 97%
“…Molecular roles of Rf genes have been thought to alter mitochondrial genome structure [15,26,35], transcription and/or post-transcriptional processing of mitochondrial genes [12,13,20,22,27,38,41] that often causes modification of translation products [ 13,36]. To understand the role ofAgropyron telosomes on the restoration of normal vigor and male fertility of the alloplasmic hybrids, we compared mitochondrial genome organization and gene expression using seedlings of one representative line showing depressed vigor and the corresponding restored and control lines.…”
Section: Introductionmentioning
confidence: 99%